HUBUNGAN BREEDING PLACE DAN RESTING PLACE TERHADAP KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI KECAMATAN SEMARANG BARAT - Tika Adelia Nurkholis Puteri; Yusniar Hanani Darundiati; Nikie Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2018)
: Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by Dengue virus and transmitted by Aedes aegypti mosquitoes. Factors that influence the incidence of DHF include physical environmental factors such as air temperature, humidity, breeding places and resting places. Breeding places can increase dengue transmission vector, the more mosquito breeding places, the more dense the DHF vector population. It is known that the last three years the number of dengue cases in 2015 in West Semarang Sub-district is 151 cases (IR 85,46), 2016 23 cases (IR 13,03), 2017 30 cases (IR 18,75). The purpose of this study was to analyze the relationship between physical environment (positive larvae breeding place, resting place) and the incidence of DHF. The type of research used is observational analytics with case control approach. The sample of this study amounted to 28 cases and 28 controls performed matching age and sex. Data collection was done by interview and observation. The data analysis used chi-square test and the magnitude of risk using odds ratio (OR). The results showed that of the three independent variables studied, there was one variable related to the occurrence of dengue fever (p = 0.001 OR = 10,389), the presence of hanging clothing (p = 1,000 OR = 2.083) and the presence of dark rooms p = 0.084 OR = 3,333). This study concluded that the presence of positive larvae Breeding Place is a risk factor for DHF incidence that has a relationship with the incidence of DBD in West Semarang District (p = 0.001).